A class of proportional integral sliding mode control with application to active suspension system - Yahaya Md. Sam, author; Johari Halim Shah Osman, author; Mohd. Ruddin Abdul Ghani, author (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL